The problem of creating a positive image of China on the International arena - Andrieieva, K.; Karlyuk, S. V. (Харківський національний університет ім. В. Н. Каразіна, 2019)
The article is devoted to the research of the problem of forming a positive image of the People’s Republic of China (hereinafter – the PRC) on the International arena. The theoretical bases of the international image of the country and the role of tourism in building up the country’s image have been elucidated, the social, political, and economic pre requisites for building up the image of PRC have been revealed.
Keywords: brand; international image; People’s Republic of China; Tibetan conflict; tourism